Empowerment strategy for people with disabilities through nonformal batik education program - Mulyono, Sungkowo Edy; Putra Widhanarto, Ghanis; Sutarto, Joko; Malik, Abdul; Shofwan, Imam (LPMPP Universitas Negeri Yogyakarta, 2023)
Efforts to improve the welfare of people with disabilities are the focus of the state as one of the ways to achieve equitable national welfare. Empowerment strengthens the presence of people with disabilities through climate growth and potential development to grow and develop into strong and independent individuals or groups of people with disabilities. This research aims to develop a strategy for empowering people with disabilities through non-formal batik education programs. This research used Developmental Research and Utilization Model (DRU Model) with a mixed qualitative and quantitative approach through analysis, development, evaluation, distribution, and acceptance. It is concluded that there are three main strategies for empowering people with disabilities: (1) awareness of people with disabilities and their parents of people by providing direction and motivation so that people with disabilities have the skills to support their future and are no longer dependent on their parents and families; (2) the formation of disability community groups to facilitate interaction among people with disabilities or with society and increase self-confidence; (3) implementation of education and training so that people with disabilities have skills for a livelihood by working in industries or entrepreneur. The value of the variable competency test positively influences the achievement of disability work with a regression coefficient of 0.07. These results indicate that if the competency test scores increase by 1%, the work performance of people with disabilities will increase by 0.07. The implication of this research is the formation of groups of people with disabilities who passed education and training with skills and livelihoods to make batik can carry out the entrepreneur and a model for developing community empowerment strategies for people with disabilities.